2011
DOI: 10.1111/j.1600-6143.2011.03524.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Listing Status Awareness: Results of a Single-Center Survey of Hemodialysis Patients

Abstract: This study surveyed hemodialysis patients in an urban transplant center serving a predominantly African American population to identify existing and potential barriers to transplantation. The survey used the Dialysis Patient Transplant Questionnaire (DPTQ) to collect self-reported data including interest in a deceased donor kidney transplant and self-reported listing status. We compared patients' survey data to their UNOS listing and computerized medical record at time of interview. Among the 116 patients surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The results are on the basis of a convenience sample of 101 urban-dwelling black patients with ESRD at two hemodialysis clinics affiliated with a university hospital in north Philadelphia that serve a largely minority lowincome patient population (53). Despite their comparatively high rate of transplant referral, our patients are similar to other patients in that many do not complete the workup step toward the waitlist (13,16,48). Although other studies show that patients with private insurance have better access to LDKT (24,25), only two of our patients had private insurance, and neither wanted an LDKT.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The results are on the basis of a convenience sample of 101 urban-dwelling black patients with ESRD at two hemodialysis clinics affiliated with a university hospital in north Philadelphia that serve a largely minority lowincome patient population (53). Despite their comparatively high rate of transplant referral, our patients are similar to other patients in that many do not complete the workup step toward the waitlist (13,16,48). Although other studies show that patients with private insurance have better access to LDKT (24,25), only two of our patients had private insurance, and neither wanted an LDKT.…”
Section: Discussionmentioning
confidence: 48%
“…The survey data were collected with the Temple University Hospital DPTQ, an instrument designed with questions validated in previous studies and questions developed by Gillespie et al (16). The DPTQ takes approximately 30 minutes to administer and is written at a 6th grade literacy level.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that a majority of dialysis patients [71.6% (11)- 94% (12)] are interested in getting a KTx. In our study, only 19% of the dialysis professionals completing this survey thought that >50% of their patients were interested in KTx.…”
Section: Discussionmentioning
confidence: 99%
“…As important as communication is between referring/primary care physicians and the transplant center, it is equally important for the transplant center to communicate the patient's status to the patient. A recent survey study of dialysis patients revealed that more than half of patients who were undergoing pretransplantation work-up were unaware of their true listing status [3]. Nearly 89% of these patients who completed the Dialysis Patient Transplant Questionnaire and were unaware of their true listing status mistakenly believed they were listed and 11% were unsure of their current status.…”
Section: Introductionmentioning
confidence: 99%